The new approach for definition of volume confined by ECR surface and its area in ECR ion source - Philippov, A.V. (Вопросы атомной науки и техники, 2008)
The volume confined by resonance surface and its area are one of the important parameters of the balance equations model for calculation of ion charge–state distribution (CSD) in electron–cyclotron resonance (ECR) ion source. The new approach for definition of these quantities is given. This approach allows to reduce the number of parameters of balance equations model.